Steeped in a culture of violence: murder, racial injustice, and other violent crimes in Texas, 1965-2020 - Jett, Brandon T.; Howell, Kenneth W. (Elma Dill Russell Spencer series in the West and Southwest, 2023)
"This collection of essays examines whether or not a culture of violence exists in modern Texas by examining trends associated with various types of violence within the state as well as the social and political responses to violent behaviors and events from 1965 to the present. Texas history is steeped in brutality and bloodshed, including conflicts between Native American tribes (such as the Comanche and Apache), confrontations between European settlers and indigenous peoples, warfare, violence against slaves, personal feuds, extralegal activities commonly practiced during the late nineteenth and early twentieth century, labor strikes and riots, battles between segregationists and civil rights activists, and myriad other incidents. While scholars have argued that industrialization and economic changes coupled with the expansion of state institutions in the late nineteenth and twentieth centuries have worked to reduce the frequency and acceptance of violence, recent evidence indicates that the general public does not agree, suggesting instead that a culture of violence has emerged, or perhaps persisted. Beginning with a broad introductory essay, the work proceeds in twelve chapters, each dealing with a specific form of violence. This important and timely collection provides valuable context to discussions on violence in general while providing a close examination of whether or not a culture of violence exists in Texas in the modern era"--